An analysis of false positive reactions occurring with the Captia Syph G EIA. Issue 5 (October 1991) - Ross, J; Moyes, A; Young, H; McMillan, A
Abstract : AIM–The Captia Syph G enzyme immuno assay (EAI) offers the potential for the rapid automated detection of syphilis antibodies. This study was designed to assess the role of other sexually transmitted diseases (STDs) in producing false positive reactions in the Captia Syph G EIA. The role of rheumatoid factor (RF) as a potential source of false positives was also analysed. METHODS–Patients who attended a genitourinary medicine (GUM) department and gave a false positive reaction with the EIA between 1988 and 1990 were compared with women undergoing antenatal testing and with the control clinic population (EIA negative) over the same time period. The incidence of sexually transmitted disease (STD) in the clinic population and the false positive reactors was measured in relation to gonorrhoea, chlamydia, genital warts, candidiasis, "other conditions not requiring treatment" and "other conditions requiring treatment." Male: female sex ratios were also compared. Ninety two RF positive sera were analysed with the EIA. RESULTS–The rate of false positive reactions did not differ with respect to the diagnosis within the GUM clinic population. The antenatal group of women, however, had a lower incidence of false positive reactions than the GUM clinic group. No RF positive sera were positive on Captia Syph G EIA testing. CONCLUSIONS–There is no cross reaction between Captia Syph G EIA and any specific STD or with RF positive sera. The lower incidence of false positive reactions in antenatal women is unexplained but may be related to physiological changes associated with pregnancy.